2022
DOI: 10.1186/s13023-022-02572-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying adult hypophosphatasia in the rheumatology unit

Abstract: Background The most frequent manifestation in adult hypophosphatasia (HPP) is musculoskeletal pain. The unspecific nature of its clinical presentation may prevent correct diagnosis. The aim of the study was to assess the prevalence of ALPL mutations in adult patients treated in rheumatological outpatient facilities with evident musculoskeletal symptoms typical for HPP. Methods Over a period of 10 years 9,522 patients were screened in the rheumatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(59 reference statements)
1
8
0
2
Order By: Relevance
“…Similarly, Feurstein et al found 5.5% of patients with at least one low ALP value under 40 UI/L, with only 13.9% of patients presenting persistent low ALP levels and musculoskeletal symptoms; they represented 0.8% of the whole population from a rheumatology outpatient clinic in Vienna specialised in rheumatology and rare bone diseases. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Feurstein et al found 5.5% of patients with at least one low ALP value under 40 UI/L, with only 13.9% of patients presenting persistent low ALP levels and musculoskeletal symptoms; they represented 0.8% of the whole population from a rheumatology outpatient clinic in Vienna specialised in rheumatology and rare bone diseases. 15 …”
Section: Discussionmentioning
confidence: 99%
“…According to a literature review, the BMD of adults with HPP only slightly decreased [ 37 , 38 , 39 ]. In contrast, higher vertebral BMD (possibly owing to excessive PPi deposition) is associated with an increased risk of fractures in adult HPP [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the global HPP Registry, the average age at diagnosis of adult HPP is 48.9 years old [ 30 ]. A study showed that the average interval from symptoms to diagnosis was 14.4 years [ 39 ]. On the other hand, the prevalence of HPP is high.…”
Section: Discussionmentioning
confidence: 99%
“…A large retrospective study identified US adult patients with persistent hypophosphatasemia and showed more frequent radiographic calcific periarthritis, diffuse idiopathic skeletal hyperostosis (DISH), and chondrocalcinosis (p < 0.001) [19]. In another case series of 29 patients with low ALP identified in a rheumatology unit, Feurstein et al demonstrated that patients with ALPL pathogenic variants/mutations have significantly more peri-articular calcifications (but also dental problems) [20]. Out of 22 adults diagnosed with hypophosphatasia, the Mayo Clinic identified radiographic calcium pyrophosphate deposition disease in 27% and documented pyrophosphate arthropathy in 14% [7], while 6 out of 16 patients had symptomatic chondrocalcinosis [21] and 21% had crystal disease in another cohort [8].…”
Section: E Calcium Pyrophosphate Crystal Deposition and Hypophosphatasiamentioning
confidence: 99%